2008
DOI: 10.1103/physrevlett.101.190602
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between Anderson and Stark Localization in 2D Lattices

Abstract: This Letter studies the dynamics of a quantum particle in 2D lattices with on-site disorder in the presence of a static field. It is shown that the particle is localized along the field direction, while in the orthogonal direction to the field it shows diffusive dynamics for algebraically large times. For weak disorder an analytical expression for the diffusion coefficient is obtained by mapping the problem to a band random matrix. This expression is confirmed by numerical simulations of the particle's dynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…( 3)] can be viewed as a distance traveled by a carrier within the time-interval (0, t). For noninteracting case ∆E(t) < 4 and r(t) < 4/F , which is the Stark localization length [22]. Here, we have found that r(t 1 ) ∼ L confirming that the finitesize effects originate from heating of the spin background when carrier repeatedly encircles the ladder.…”
supporting
confidence: 72%
“…( 3)] can be viewed as a distance traveled by a carrier within the time-interval (0, t). For noninteracting case ∆E(t) < 4 and r(t) < 4/F , which is the Stark localization length [22]. Here, we have found that r(t 1 ) ∼ L confirming that the finitesize effects originate from heating of the spin background when carrier repeatedly encircles the ladder.…”
supporting
confidence: 72%
“…Systematic variations in site energies or coupling strengths can also cause localization [31], with the well-known instance of Bloch oscillations and Stark localization deriving from a linear bias in site energies [32]. Both systematic and random variations in site energies remove the symmetry necessary for Bloch's theorem, so it is not surprising that their combination leads to localization as well [33,34]. Adding disorder into the graph structure also usually causes localization [35] (although such disorder can also reduce localization if it makes an already disordered graph more connected [36]).…”
Section: Coherent Dynamicsmentioning
confidence: 99%
“…In this paper, we want to extend the spectral analysis to the case of two-dimensional BHMs with strong interparticle interactions. The dynamics of two-dimensional tight-binding systems was studied before in the noninteracting case [17], or in the specific case of a four mode interacting system [18]. Analyzing different minimal models of up to a 3x3 square lattice, we will see how the geometry of the lattice and the number of permitted couplings (i.e.…”
Section: Introductionmentioning
confidence: 99%